Study on Solution-Processable Polypyrrole-Based Conducting Polymers - Fu, Haoyu (University of Waterloo, 2023)
Due to the adjustable conductivity, cost-effective synthesis, and easy device fabrication, conducting polymers have wide-ranging applications in numerous areas, including sensors, solar cells, supercapacitors, and electrodes. Among conducting polymers, polypyrrole (PPy) has attracted lots of attention because of its high conductivity, biocompatibility, and mass producibility. However, PPy is insoluble in most solvents, which lowers its processability and limits its application. In the past few decades, many works by researchers around the world have been done to improve the solubility of PPy. Unfortunately, the two major strategies, including doping with large contour ions and introducing an alkyl sidechain to the PPy backbone, were found to significantly decrease the conductivity of PPy by several orders of magnitude. For the doping method, the restricted dopant options limit the conductivity of PPy, whereas the alkyl sidechains twist the polymer structure thus influencing the conductivity. As a result, new methods need to be explored to improve the solubility of PPy without sacrificing its electrical properties. In this work, two strategies were applied to address this problem. The first is to introduce an alkyl carbamate sidechain to the PPy backbone; the carbamate sidechain can solubilize the polymer, while allowing thermal removal at mild temperatures. Thus, after solution processing, the obtained polymer film can be thermally annealed to remove the sidechain, thereby recovering the PPy structure and conductivity. The second one is to introduce an alkoxy sidechain at the N position of the PPy backbone. This sidechain has less steric hindrance than the alkyl sidechain. Therefore, the PPy with the alkoxy sidechain was expected to have a more planar backbone compared to the alkyl chain-substituted counterpart and as such was expected to have higher conductivity. We first designed, synthesized, and characterized poly(2-ethylhexyl 1H-pyrrole-1-carboxylate) (PEPC), with a 2-ethylhexyl carbamate chain substituted at the N position of PPy. Different synthetic routes were explored and optimized, including organometallic polymerization and oxidative polymerization. The desired polymer was successfully synthesized and was soluble in various organic solvents, including acetone, dichloromethane, and chloroform. Polymer films in a thickness of 50-60 nm could be deposited from the PEPC chloroform solution on a SiO2/Si substrate, which satisfies requirements for sensor applications. 1 However, the 2-ethylhexyl carbamate sidechain could not be completely removed by thermal annealing and acid cleavage due to the primary structure of ethylhexyl aliphatic chain of the carbamate being reluctant to undergo decomposition. This led to a low conductivity of the PEPC thin films. In the future, a carbamate sidechain with a different secondary or tertiary structure may be applied, allowing easy removal of the sidechain and restoration of the PPy structure. Poly[1-((2-ethylhexyl)oxy)-1H-pyrrole] (PEOP) with a 2-(ethylhexyl)oxy sidechain at the N position of PPy was designed, and its synthesis was explored. Due to the difficulties in the synthesizing and purifying the monomer, 1-((2-ethylhexyl)oxy)-1H-pyrrole, the desired PEOP was not obtained. However, it was found that the 2-(ethylhexyl)oxy sidechain can undergo a thermolysis process under milder temperatures than the alkyl carbamate sidechain, as evidenced by FTIR and TGA results. Therefore, the thermal instability of 2-(ethylhexyl)oxy and other alkoxy sidechains on nitrogen may allow the development of other polymers that require the sidechains to be thermally removable at mild temperatures. In addition, new synthetic approaches can be explored in the future to obtain a more structurally defined PEOP.
Keywords: Conducting Polymer; Polypyrrole; Organometallic Synthesis; Organic Semiconductor